(untitled) (Computer systems and information technologies, 2024)
The purpose of this article is the development and description of the method of organizing inter-module data exchange, that is based on the parametric presented subsystems, as well as the evaluation of the effectiveness of the developed multiprocessor computing systems. The authors propose a method of organizing inter-modular exchanges, which is based on the parametric presented subsystem. When developing programs using parallelization algorithms, parameters are used that set specific values for the subsystem. These values are determined during the formation of the subsystem. This makes the program independent of the graph of subsystem inter-module connections, on the basis of which this program will be implemented. The effectiveness of the computer system depends on a set of characteristics, which include: performance, reliability, probability of results, stability, manufacturability and others. To compare computer systems as a criterion of efficiency, it is necessary to adopt a comprehensive indicator that will take into account the main indicators. The real efficiency of a computer system is determined by the time it fulfils its functional purpose. Accordingly, the more reliable the system, the more relative time it is used for its intended purpose and the greater its efficiency. Thus, when comparing computer systems, it is necessary to compare their performance taking into account the real reliability of the system. At the same time, depending on the classes of problems being solved, the influence of various indicators (including reliability) on the efficiency of the system changes. Based on the results of the research, the following conclusions can be drawn: the most effective are the computer systems that are implemented on the developed MO. This fact is clearly visible from the comparison of the time spent on calculating not only the test task, but also when calculating the test equation with the test parameters.